2020
DOI: 10.1002/aur.2287
|View full text |Cite
|
Sign up to set email alerts
|

Common vs. Distinct Visuomotor Control Deficits in Autism Spectrum Disorder and Schizophrenia

Abstract: Autism spectrum disorder (ASD) and schizophrenia (SCZ) are neurodevelopmental disorders with partly overlapping clinical phenotypes including sensorimotor impairments. However, direct comparative studies on sensorimotor control across these two disorders are lacking. We set out to compare visuomotor upper limb impairment, quantitatively, in ASD and SCZ. Patients with ASD (N = 24) were compared to previously published data from healthy control participants (N = 24) and patients with SCZ (N = 24). All participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 78 publications
3
7
0
Order By: Relevance
“…Interestingly, previous studies have reported alterations in motor anticipation in ASD (e.g. Carment et al, 2020;Crippa et al, 2015;Fabbri-Destro et al, 2009;Forti et al, 2011). The findings of a diagnosis-by-sex interaction on kinematic PC4 partially resembled Sacrey and colleagues' (2018) assessment of the motor act of reaching-to-grasp in children at high/ low risk of ASD.…”
Section: Discussionsupporting
confidence: 59%
“…Interestingly, previous studies have reported alterations in motor anticipation in ASD (e.g. Carment et al, 2020;Crippa et al, 2015;Fabbri-Destro et al, 2009;Forti et al, 2011). The findings of a diagnosis-by-sex interaction on kinematic PC4 partially resembled Sacrey and colleagues' (2018) assessment of the motor act of reaching-to-grasp in children at high/ low risk of ASD.…”
Section: Discussionsupporting
confidence: 59%
“…Here we got a fine distinction of visuomotor phenotypes among sport students thanks to the VMVR task associated to the capture of head movements. Getting finer analyses of visuomotor integration abilities has several benefits such as screening neurological soft signs 41 or tracking early progress in rehabilitation 13 and vision training programs 14 . Here by adding head movement analysis, we discriminated individual behaviors in eye-hand coordination among young and healthy people, which is promising for exploring visuomotor phenotypes in more heterogeneous groups.…”
Section: Discussionmentioning
confidence: 99%
“…In such people, reading and verbalizing numbers while coordinating eye-hand movements certainly represents very little difficulty in a dual-task setting. Rather, placing high mental demand relatively to the user’s cognitive capacity makes sense as demonstrated recently to distinguish common and distinct visuomotor impairments in autism and schizophrenia 41 . This is where VMVR has obvious advantages because of VR flexibility to design cognitive demands that can be adapted to the user (either children, elderly or athletes) as well to their impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Miller et al (2021) reported that more than 90% of autistic children met the criteria for clinically significant motor difficulties on the Movement Assessment Battery for Children, Second Edition (MABC‐2; Henderson et al, 2007), the gold‐standard standardized assessment of motor ability. Examining specific motor skills, researchers have measured differences in quiet standing (Lim et al, 2017), leaning (Miller et al, 2019; Wang et al, 2016), stepping (Bojanek et al, 2020), reaching (Glazebrook et al, 2006), grasping (Carment et al, 2020; Mosconi et al, 2015; Travers et al, 2017), catching (Chen et al, 2019), and tool use (Mostofsky et al, 2006). These motor difficulties are implicated in social, cognitive, and adaptive function and in turn, have implications for autistic children's quality of life and mental health (Tamplain & Miller, 2020).…”
Section: Introductionmentioning
confidence: 99%